(untitled) (Journal of science and technology exploration, 2026)
The new quality agricultural productive forces are the core driving force for promoting agricultural modernization and high-quality development. Based on the panel data of 31 provinces in China from 2012 to 2022, this paper empirically examines the impact of new quality agricultural productive forces on agricultural product export trade and its mechanism of action. The research findings are as follows: (1) The new quality agricultural productive forces significantly promote the growth of agricultural product export trade, and this conclusion remains valid after robustness checks; (2) The mechanism analysis indicates that agricultural technical efficiency plays a partial mediating role in the promotion of exports by new quality agricultural productive forces; (3) Agricultural insurance has a significant positive moderating effect, which can enhance the promoting effect of new quality agricultural productive forces on exports. This study provides empirical evidence for understanding the relationship between agricultural technological innovation and trade competitiveness, and offers directions for policy formulation: it is necessary to continue to increase support for agricultural science and technology, improve the agricultural insurance system, and further unleash the export-promoting effect of new quality agricultural productive forces by enhancing technical efficiency.